A proposed conceptual framework for mobile health technology adoption among employees at workplaces in Malaysia - Sari H.; Othman M.; Al-Ghaili A.M. (Springer Verlag, 2023)
Behavioral research; mHealth; Personnel; Soft computing; Wearable technology; Health behaviors; Health technology; Technology acceptance model; UTAUT2; Workplace health; Economic and social effects